(untitled) (Research, Society and Development, 2023)
With technological advances, more and more research has been done to offer innovations, devices and biocompatible materials for the field of dentistry. The literature confirms the benefits of using these technologies in dental offices. Clinicians working in the field of endodontics must be aware of all the features and capabilities of instruments that are possible to use when performing root canal treatment. Thus, the aim of this study is to review and evaluate the literature on the effectiveness and benefits of rotary files in endodontic treatment. For the construction of this article, a bibliographical survey was carried out in the databases SciVerse Scopus, Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) and ScienceDirect, with the help of the Mendeley reference manager. The articles were contemplated between the years 2000 to 2023. Rotary instruments reduce the professional’s work time, reduce the possibilities of cross-contamination due to the repetitive use of the instrument, as they are discarded after each procedure. The systems present excellent results and when used following the recommendations and indications, they prevent iatrogenic events during the preparation. Finally, more studies need to be done using large sample sizes to assess the comparative efficiency of rotary and manual instrumentation. A definitive conclusion cannot be drawn from the available literature, however, the choice of treatment protocol can be made based on clinical requirements.